Risk factors for implant failure: a retrospective study in an educational institution using GEE analyses - Marcelo BORBA; Daniel DELUIZ; Eduardo José Veras LOURENÇO; Luciano OLIVEIRA; Patrícia Nivoloni TANNURE (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract This study aimed to evaluate dental implant outcomes and to identify risk factors associated with implant failure over 12 years via dental records of patients attending an educational institution. Dental records of 202 patients receiving 774 dental implants from 2002 to 2014 were analyzed by adopting a more reliable statistical method to evaluate risk factors with patients as the unit [generalized estimating equation (GEE)]. Information regarding patient age at implantation, sex, use of tobacco, and history of systemic diseases was collected. Information about implant location in the arch region and implant length, diameter, and placement in a grafted area was evaluated after 2 years under load. Systemic and local risk factors for early and late implant failure were studied. A total of 18 patients experienced 25 implant failures, resulting in an overall survival rate of 96.8% (2.84% and 0.38% early and late implant failures, respectively). The patient-based survival rate was 91.8%. GEE univariate and multivariate analyses revealed that a significant risk factor for implant failure was the maxillary implant (p = 0.006 and p = 0.014, respectively). Bone grafting appeared to be a risk factor for implant failure (p = 0.054). According to GEE analyses, maxillary implants had significantly worse outcomes in this population and were considered to be a risk factor for implant failure. Our results suggested that implants placed in a bone augmentation area had a tendency to fail.